Local Drivers of Change in Southern Ocean Ecosystems: Human Activities and Policy Implications - Grant, Susie M.; Waller, Cath L.; Morley, Simon A.; Barnes, David K. A.; Brasier, Madeleine J.; Double, Mike C.; Griffiths, Huw J.; Hughes, Kevin A.; Jackson, Jennifer A.; Waluda, Claire M.; Constable, Andrew J. (Frontiers in Ecology and Evolution, 2021)
Local drivers influence Southern Ocean ecosystems at a particular location or series of locations. We consider marine and land-derived pollution, non-indigenous species, tourism and other human visits, exploitation of marine resources, recovery of marine mammals, and coastal change as a result of ice loss, in terms of their historic and current extent, and their interactions with the Southern Ocean environment. We summarize projected increases or decreases in the influence of local drivers, and projected changes to their geographic range, concluding that the influence of non-indigenous species, fishing, and the recovery of marine mammals are predicted (with medium to high confidence) to increase in the future across all MEASO areas. Local drivers can be managed regionally, and we identify existing governance frameworks as part of the Antarctic Treaty System and other instruments which may be employed to mitigate or limit their impacts on Southern Ocean ecosystems.